Pursed Lips Breathing with Balloon Enhancing Airway Clearance in Children with Pneumonia - Musviro; Arini Fitria; Nurul Hayati; Laili Nur Azizah; Anggia Astuti (KHD Production, 2025)
Pneumonia can pose a serious threat to children's health. In pneumonia, increased lung secretions obstruct the airways, affecting breathing, especially in children who cannot expel sputum alone. If not treated immediately, this condition can be fatal. This study aimed to provide nursing care for children with nursing problems of ineffective airway clearance with Pursed Lips. Breathing using balloons can help improve gas exchange, which is observed by increasing oxygen saturation in the body and can help expel secretions. Participants in this study were pneumonia patients aged 3-5 years who were treated in the Bougenville Room of Dr. Haryoto Hospital, Lumajang, with nursing problems of Ineffective Airway Clearance and were not allergic to balloons. Data collection used interviews, observations, and documentation studies. The results of the assessment showed that An. A male, 5 years old, has a weak general condition, ineffective cough, sputum, additional breathing sounds of rhonchi, and an increased respiratory rate. The nursing problem that occurred was ineffective airway clearance. The interventions carried out refer to the Indonesian Nursing Intervention Standards (SIKI) intervention, namely airway management, respiratory monitoring, and Pursed Lips Breathing (PLB) actions. To attract children's interest, PLB uses balloons conceptualized as balloon play therapy, whose mechanism is similar to PLB with an atraumatic care approach. After nursing care for 4 days, the goals were achieved. Namely, changes in effective coughing increased, sputum decreased, additional breath sounds were absent, breathing patterns changed, and breathing frequency improved. Pursed Lips Breathing (PLB) can increase alveolar expansion in each lung lobe so that alveolar pressure increases and secretions can be pushed into the airway during expiration. PLB can be carried out to increase knowledge as an innovative intervention in treating children with pneumonia diagnosed with ineffective airway clearance.